2020
DOI: 10.1002/marc.202000098
|View full text |Cite
|
Sign up to set email alerts
|

Substrate‐Independent, Reversible, and Easy‐Release Ionogel Adhesives with High Bonding Strength

Abstract: structures to enhance the van der Waals interactions with the substrate. [5-7] Reversible and stimuli-responsive adhesives can also be fabricated based on stimuliresponsive polymers or polymer systems involving reversible and dynamic molecular interactions, such as the introduction of temperature or light isomerization groups, [8-10] dynamic covalent bonds [11,12] (e.g., Diels-Alder reaction, disulfide bonds) and reversible noncovalent interactions [13-20] (e.g., hydrogen bonds, metal-ligand and host-gust inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 34 publications
0
54
0
Order By: Relevance
“…[44,45] During the underwater adhesion of ionogels, the hydration layer on the substrate surface can be destroyed due to the hydrophobicity of the ionogels. Then, various interactions, such as ion-dipolar, [31,46,47] dipolar-dipolar, [48][49][50] metal complexation, [51] electrostatic, [44,52] cation-π interactions, [44] and van der Waals interactions, [53] can be formed between the ionogels and different substrates (Figure S8, Supporting Information). Therefore, underwater strong adhesion can be formed.…”
Section: Resultsmentioning
confidence: 99%
“…[44,45] During the underwater adhesion of ionogels, the hydration layer on the substrate surface can be destroyed due to the hydrophobicity of the ionogels. Then, various interactions, such as ion-dipolar, [31,46,47] dipolar-dipolar, [48][49][50] metal complexation, [51] electrostatic, [44,52] cation-π interactions, [44] and van der Waals interactions, [53] can be formed between the ionogels and different substrates (Figure S8, Supporting Information). Therefore, underwater strong adhesion can be formed.…”
Section: Resultsmentioning
confidence: 99%
“…The results are displayed in Figure a, and the adhesive strength of nanocomposite ionogels to glass, plastic, aluminum, and cooper reached 13.21 ± 0.68 kPa, 24.31 ± 2.52 kPa, 23.20 ± 2.29 kPa, and 2.24 ± 1.52 kPa, respectively. The P­(AAm- co -HEA)-Laponite XLG ionogel exhibited the highest adhesion strength to the copper sheet, probably due to the coordination interactions and hydrogen bonding synergistic effects between the ionogel and copper. , The corresponding test curves of the adhesive strength to different substrates are depicted in Figure b. In addition, the repeated and durable adhesion performance of nanocomposite ionogels was investigated by 10-time consecutive adhesion/peeling-off tests (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The P(AAm-co-HEA)-Laponite XLG ionogel exhibited the highest adhesion strength to the copper sheet, probably due to the coordination interactions and hydrogen bonding synergistic effects between the ionogel and copper. 58,59 The corresponding test curves of the adhesive strength to different substrates are depicted in Figure 5b. In addition, the repeated and durable adhesion performance of nanocomposite ionogels was investigated by 10-time consecutive adhesion/peeling-off tests (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the loss of adhesion against wet or oil-fouling surfaces, the attachment systems of organisms capable of forming adhesion in a natural environment have been widely studied. Inspired by the fascinating adhesion capacity of living organisms, much effort has been devoted to the elaborate structure design and composition selection of adhesives, for example, the biostructures, mussel-inspired and catechol-based polymeric materials, and ionic hydrogels. , These strategies significantly enhance the underwater adhesion of adhesives. However, unlike numerous studies for antiwater adhesives, anti-oil-fouling ones are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The tape should be soft with high interfacial adhesive energy to realize fast bonding, which usually sacrifices the cohesive energy and vice versa. , Although no scaling theory guides us to overcome such a trade off, it is required to obey Cannikin’s law, that is, not sacrificing one performance distinctively, the other performance is improved significantly. Recently, there are six approaches to relieve this dilemma: (1) combining dynamic bonds with bioinspired surface drainage architecture or catechol moiety, , (2) synergetic effect between a hydrophobic backbone and hydrophilic adhesive side branches, ,, (3) modification of poly­(ionic liquid)­s (PILs), ,, (4) sequence-controlled poly­(cation-π)­s, ,,, (5) introduction of dual cross-linking networks, , and (6) composite with nanofillers. Nevertheless, abovementioned adhesives with a high adhesion strength usually are glue-type adhesives, which need UV, heat, an extra cross-linking agent, or long-time to cure, while hydrogel-type adhesives still cannot achieve high bonding strength limited by their weak cohesive strength.…”
Section: Introductionmentioning
confidence: 99%